(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The article discusses methods of teaching the plot and compositional structure of a literary work. It reveals the importance of identifying the connection between the stages of plot development and compositional elements during literary analysis. Through the analysis of the structural features of a literary work, ways to develop students’ artistic perception and creative thinking abilities are determined.